Hepatitis B cure: How and when - Dusheiko, Geoffrey; Valenti, Luca (Liver international, 2021)
Background First‐ and second‐ generation new treatments are being evaluated to provide a cure for hepatitis B. The life cycle of HBV includes several well‐ categorized steps that are targets for new treatments. A cure remains a major challenge even if it is measured by HBsAg seroclearance alone. The notion of a functional cure of hepatitis B has been accepted, while a partial functional cure has been more tentatively defined as a decline in HBsAg concentrations to lower levels after finite treatment. Methods More profound suppression of hepatitis B replication through the addition of capsid inhibitors with nucleoside analogues could improve patient prognosis and a sustained treatment response. Several strategies are being evaluated to achieve a cure: (a) deepening inhibition of HBV replication or (b) a reduction in HBsAg presentation for HBsAg seroclearance. Results Fortunately, there are signs of important progress in the treatment of hepatitis B including improved on‐ treatment reductions or seroclearance of HBsAg in phase 2 studies that was not achieved with chain terminators and inhibitors of initiation of DNA synthesis. Progress in immunomodulatory therapy has lagged behind that of antiviral therapy. Conclusions Increasing the multilayered impaired and dysfunctional immune response in hepatitis B is perhaps more likely and feasible after a reduction in host antigen burden. Other potential experimental strategies include CRISPR‐ Cas9 genome‐ editing nucleases to specifically target and cleave cccDNA or novel monoclonal antibodies.